Malaysia : 2012 Article IV Consultation. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2013)
This report discusses Malaysia's economic accomplishment and other economic reforms. Malaysia has attained a strong growth in 2012, and a robust growth is expected in the next term. The financial position of Malaysia is sound and supported by a strong regulatory framework with high bank capitals, international reserves, and refined monetary and financial policies. Fiscal policies need to be restructured, and public financial management needs to be strengthened to deal with risks. The authorities expected Malaysia to be a high-income nation by 2020.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet